2020
DOI: 10.1002/cphc.201901161
|View full text |Cite
|
Sign up to set email alerts
|

Probing Viscosity of Co‐Polymer Hydrogel and HeLa Cell Using Fluorescent Gold Nanoclusters: Fluorescence Correlation Spectroscopy and Anisotropy Decay

Abstract: Fluorescence dynamics of gold nanoclusters (Au9 and Au25) are studied in the complex and crowded environment of a triblock co‐polymer (F127) hydrogel and inside cervical cancer cell, HeLa. In the hydrogel, spherical micelles of F127 remain immobilized with a hydrophobic core (PPO) and a hydrophilic corona (PEO) region. The fluorescence anisotropy decay suggests that the timescale of rotational relaxation in the hydrogel is similar to that in bulk water (viscosity ∼1 cP). From fluorescence correlation spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 54 publications
(165 reference statements)
0
13
0
Order By: Relevance
“…[1][2][3][4] At the same time, it has good development and wide application prospects in sensing, coding, photoelectron.etc. [5][6][7][8] Polyurethane is more suitable to be used as matrixes of polymeric fluorescent dye due to its advantages such as adjustable structure, stable performance and diverse processing methods, etc., and is of high interest. [9][10][11][12] Polyurethanebased fluorescent dye is polymeric fluorescent dyes formed by anchoring monomeric fluorescent dye to polyurethane chains by chemical bonds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] At the same time, it has good development and wide application prospects in sensing, coding, photoelectron.etc. [5][6][7][8] Polyurethane is more suitable to be used as matrixes of polymeric fluorescent dye due to its advantages such as adjustable structure, stable performance and diverse processing methods, etc., and is of high interest. [9][10][11][12] Polyurethanebased fluorescent dye is polymeric fluorescent dyes formed by anchoring monomeric fluorescent dye to polyurethane chains by chemical bonds.…”
Section: Introductionmentioning
confidence: 99%
“…This kind of material is not only safe, non‐toxic, very low mobility and permeability, but also has the characteristics of absorption peak width, high quantum yield and stable luminescence performance [1–4] . At the same time, it has good development and wide application prospects in sensing, coding, photoelectron.etc [5–8] …”
Section: Introductionmentioning
confidence: 99%
“…Several groups have demonstrated that the luminescence of MNCs is highly dependent on solvent viscosity, as the viscosity is one of decisive factors affecting the rigidity of the surrounding environment of MNCs. [63–65]…”
Section: Luminescence Propertiesmentioning
confidence: 99%
“…To analyze the data obtained from the shear rate for each of the operating conditions proposed in Table 6, it was decided to compare these with maximum shear values of common cell strains used in biotechnology. Data were taken from seven different cell strains: the bacterium Escherichia coli (EC), the yeast Saccharomyces cerevisiae (SC) [29], the mammalian Chinese hamster ovary (CHO) cell [30,31], Aspergillus glaucus (AG) [32], Trichoplusia ni (NT-368) and Spodoptera frugiperda (SF-9) [33] and HeLa cells [34,35]. The properties of the cells and their cultures, such as shear rate and viscosity, are presented in Table A3.…”
Section: Shear Ratementioning
confidence: 99%